PENGARUH INOVASI PRODUK DAN SOSIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MUSLIM ES TEH INDONESIA DENGAN REFERENSI GROUP SEBAGAI VARIABEL PEMODERASI - Teguh, Nur Muhammad; Cahyono, Edi (Journal MISSY (Management and Business Strategy), 2024)
Purchasing decisions are purchases that refer to the process of choosing one option among several available options. To obtain the purpose of purchasing decisions, of course, it requires a process of integrating attitudes and knowledge to analyze ultimately choosing between two or more alternative actions. This study aims to analyze the direct and indirect influence of product innovation, and social media marketing on purchasing decisions, with reference groups as moderating variables on Indonesian Iced Tea consumers with a sample of 97 respondents. The research data was obtained from a questionnaire that had been distributed and then tested using SPSS V25. From the data analysis that has been carried out, it shows that: (1) Product innovation has a positive and significant effect on purchasing decisions (2) Social media marketing has a positive and significant effect on purchasing decisions (3) Product innovation is able to moderate reference groups on purchasing decisions (4) social media marketing is able to moderate reference groups on purchasing decisions. Keywords : Product innovation; Social media marketing; Purchasing decisions; reference groups